Communication strategy of Tourism Departement Yogyakarta in promoting tourism during the COVID-19 pandemic - Firdaus, Nalendra Putra; Anggraeni, Sinta; Hariyanti, Nunik (Universitas Ahmad Dahlan, 2023)
Tourism is a sector that is a mainstay for the City of Yogyakarta. The existence of the COVID-19 pandemic has had a significant impact on the Yogyakarta City tourism sector. Department of Tourism of Yogyakarta, a government agency responsible for tourism conditions, should have a strategy to deal with these conditions. This research was conducted to find out how Department of Tourism of Yogyakarta carried out the communication strategy in promoting tourism during the COVID-19 pandemic. The research method used is qualitative with a case study approach, and data collection is carried out using interviews and observations. The results of this study indicate Department of Tourism of Yogyakarta has a strategy for dealing with a pandemic situation by creating a new tagline,